Implementing Fair Housing Zoning in Boston: Re-envisioning Structures for Community Engagement - Duarte, Andrea. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Laurie Goldman.; Keyword: Urban planning.